Schriftexegese als Voraussetzung für Emil Brunners frühe dialektischen Soteriologie anhand des Beispieltexts Lk 15,11–32 - Fabienne STEINER (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
Dialectical Soteriology using the example of Lk 15:11–32. In my article, I would like to show Emil Brunner’s early thoughts and statements, which he reveals in his sermons in Obstalden. These sermons are still unknown and unpublished. It is mostly claimed that Brunner entered in a modern and dialectical phase because of his colleague in the Reformed Church, Karl Barth. The truth is that they later had intense discussions about theses and antitheses in their dialectic phase. Brunner, however, formulates new dialectical thoughts earlier than Barth – for example, already in 1917 on dialectical soteriology by using the text of Lk 15:11–32. In his sermons, he reflects several arguments of modern theology and defines, for example, God as thesis, lost person as antithesis, and saved person as synthesis. A detailed exegesis leads in the resolution of what follows from an encounter with God, namely being at home in safety.